Multi-technical approach for the characterization of polychrome decorative surfaces at Spanish Mission Churches in Nueva Vizcaya (Chihuahua, Mexico). Issue 2 (16th December 2019) - Muñoz-Alcocer, Karla; Fuster-López, Laura; Vázquez de Ágredos-Pascual, Ma. Luisa; Izzo, Francesca Caterina; Picollo, Marcello; Bartolozzi, Giovanni; Vega, Jose Humberto; Maldonado Escobar, Diana; Mitrani, Alejandro; Maynez, Miguel Ángel; Casanova-González, Edgar; Rangel-Chávez, Isaac; et al.
ABSTRACT: An interdisciplinary and multi-institutional group of science and art conservation specialists has provided new insight into the painting materials used in the polychrome walls and wooden ceilings in four seventeenth century Spanish colonial churches of Nueva Vizcaya (Chihuahua, Mexico). A multi-analytical study of the decorative surfaces was performed in situ using spectroscopic approaches (XRF, FORS), False Colour Infrared Reflectography – IRFC, as well as micro sampling for ATR-FTIR, LM and GC/MS laboratory analyses. A survey of natural resources were also studied by ATR-FTIR and LM to elucidate the natural occurrence of a select number of materials found in the surrounding areas of the churches. The present paper presents a multi-analytical study and characterization of green, red-orange and black colour pigments and binders selected from the decorative surfaces. The aim of this study is to highlight relationships between local materials and those from the original polychrome ceilings, in order to understand the material and technological influences that converged in the Spanish colonial architecture of northern Mexico. GRAPHICAL ABSTRACT: